Serological evidence of inter-epizootic/inter-epidemic circulation of Rift Valley fever virus in domestic cattle in Kyela and Morogoro, Tanzania. - Mirende Kichuki Matiko; Linda Peniel Salekwa; Christopher Jacob Kasanga; Sharadhuli Idd Kimera; Magnus Evander; Wambura Philemon Nyangi (Public Library of Science (PLoS), 2018)
BACKGROUND:Tanzania is among the Rift Valley fever (RVF) epizootic/endemic countries in sub Saharan Africa, where RVF disease outbreaks occur within a range of 3 to 17-year intervals. Detection of Rift Valley fever virus (RVFV) antibodies in animals in regions with no previous history of outbreaks raises the question of whether the disease is overlooked due to lack-of effective surveillance systems, or if there are strains of RVFV with low pathogenicity. Furthermore, which vertebrate hosts are involved in the inter-epidemic and inter-epizootic maintenance of RVFV? In our study region, the Kyela and Morogoro districts in Tanzania, no previous RVF outbreaks have been reported. METHODOLOGY:The study was conducted from June 2014 to October 2015 in the Kyela and Morogoro districts, Tanzania. Samples (n = 356) were retrieved from both the local breed of zebu cattle (Bos indicus) and Bos indicus/Bos Taurus cross breed. RVFV antibodies were analyzed by two enzyme-linked immunosorbent assay (ELISA) approaches. Initially, samples were analyzed by a RVFV multi-species competition ELISA (cELISA), which detected both RVFV IgG and IgM antibodies. All serum samples that were positive with the cELISA method were specifically analysed for the presence of RVFV IgM antibodies to trace recent infection. A plaque reduction neutralization assay (PRNT80) was performed to determine presence of RVFV neutralizing antibodies in all cELISA positive samples. FINDINGS:Overall RVFV seroprevalence rate in cattle by cELISA in both districts was 29.2% (104 of 356) with seroprevalence rates of 33% (47/147) in the Kyela district and 27% (57/209) in the Morogoro district. In total, 8.4% (30/356) of all cattle sampled had RVFV IgM antibodies, indicating current disease transmission. When segregated by districts, the IgM antibody seroprevalence was 2.0% (3/147) and 12.9% (27/209) in Kyela and Morogoro districts respectively. When the 104 cELISA positive samples were analyzed by PRNT80 to confirm that RVFV-specific antibodies were present, the majority (89%, 93/104) had RVFV neutralising antibodies. CONCLUSION:The results provided evidence of widespread prevalence of RVFV antibody among cattle during an inter-epizootic/inter-epidemic period in Tanzania in regions with no previous history of outbreaks. There is a need for further investigations of RVFV maintenance and transmission in vertebrates and vectors during the long inter-epizootic/inter-epidemic periods.